2022
DOI: 10.1371/journal.pcbi.1009935
|View full text |Cite
|
Sign up to set email alerts
|

Urgent need for consistent standards in functional enrichment analysis

Abstract: Gene set enrichment tests (a.k.a. functional enrichment analysis) are among the most frequently used methods in computational biology. Despite this popularity, there are concerns that these methods are being applied incorrectly and the results of some peer-reviewed publications are unreliable. These problems include the use of inappropriate background gene lists, lack of false discovery rate correction and lack of methodological detail. To ascertain the frequency of these issues in the literature, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 43 publications
0
63
0
Order By: Relevance
“…Other authors reported potential problems of functional enrichment analysis [17][18][19][20][21] and described best practices in the past [22,23], but we believe that our guidelines are easier to follow and to understand by all users, including students and beginners.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported potential problems of functional enrichment analysis [17][18][19][20][21] and described best practices in the past [22,23], but we believe that our guidelines are easier to follow and to understand by all users, including students and beginners.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with similarity measures, which can measure semantic overlap, such approaches can advance the interpretation biclustering results and method evaluations. Biological enrichment analysis can be sensitive to the exact content of biclusters and moreover can be affected by the enrichment test methodology and applied thresholds, for example (71). Therefore, GO enrichment results alone do not suffice to compare and evaluate biclustering methods and in fact may be misleading if not placed into a bicluster coherence context.…”
Section: Discussionmentioning
confidence: 99%
“…Genes whose classi cation as hypo-or hyper-variable con rmed by cross-validation were additionally analysed for over-representation using the ConsensusPathDB (Kamburov, Stelzl et al 2012). According to best practice for pathway/functional analyses (e.g., the over-representation analysis used in this work), a gene set is compared to a given list of total genes measured in an experiment, called background (Wijesooriya, Jadaan et al 2022). As such, gene lists per radiation dose after exclusion of bimodally expressed genes were used (Additional File 3).…”
Section: Gene Ontology Over-representation Analysismentioning
confidence: 99%